2020
DOI: 10.1021/acsnano.9b08460
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Induce Tumor Vessel Normalization and Impair Metastasis by Inhibiting Endothelial Smad2/3 Signaling

Abstract: Gold nanoparticles (AuNPs) are a promising nanomaterial due to their drug-delivery properties and inherent anti-neoplastic activity. Here, we focused on the anti-neoplastic effects of an improved targeting polymer and folic acidmodified gold nanoparticles (AuNPP-FA) without therapeutic drugs. AuNPP-FA inhibited tumor proliferation both in vitro and in vivo, and tumor metastasis was controlled in vivo. We also found that, in addition to inhibiting tumor angiogenesis, AuNPP-FA normalized tumor vasculature by inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 53 publications
0
51
0
Order By: Relevance
“…[ 72,73 ] It was recently shown that gold nanoparticles can accomplish this, along with inhibiting angiogenesis, by disrupting the signaling between tumor cells and endothelial cells. [ 74,75 ]…”
Section: The Entry Of Nanoparticles Into the Tumor Microenvironmentmentioning
confidence: 99%
“…[ 72,73 ] It was recently shown that gold nanoparticles can accomplish this, along with inhibiting angiogenesis, by disrupting the signaling between tumor cells and endothelial cells. [ 74,75 ]…”
Section: The Entry Of Nanoparticles Into the Tumor Microenvironmentmentioning
confidence: 99%
“…Meanwhile, some reports have highlighted the effect of mediating tumor vascular normalization of AuNPs. Huang et al (2020) focused on a model, named targeting polymer and folic acid-modified gold nanoparticles (AuNPP-FA), which can both restrain tumor angiogenesis and promote vascular normalization. It is because of the increased infiltration of CD3 + CD8 + T lymphocytes that the immunotherapeutic response was enhanced by decreasing vascular permeability and improving vascular perfusion.…”
Section: Application Strategies Of Aunps To Improve the Tumor Microenvironmentmentioning
confidence: 99%
“…Therefore, reshaping the PTME to restore the homeostatic microenvironment is a promising approach to stifle the earliest steps of metastasis initiation. By encapsulating various therapeutic agents and their intrinsic properties, NPs may serve a purpose to restrain the invasion and migration of tumor cells, thus preventing the seeds detaching from normalized primary soil ( Table 1 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ).…”
Section: Targeting the Primary Soil By Nano-dds: Preventing The Metastatic Disseminationmentioning
confidence: 99%
“… Target Role in the metastatic cascade Strategy Advantage Ref. Hypoxia Promote invasion, EMT, angiogenesis and formation of PMN Increase in situ generation of oxygen Relieve oxygen tensions 26 Enhance tumor-targeting oxygen delivery Inhibit HIF signal pathways 27 Decrease oxygen consumption Reduce the metastatic potential of tumor cells 28 Silence the HIF pathway Reverse the immunosuppressive microenvironment 29 , 30 Acidosis Enhance local invasion, migration and angiogenesis Use basic materials or drugs to neutralize acidity Restrain the invasion and migration of tumor cells 31 , 32 Restrain the cellular efflux of lactate 33 Relieve hypoxia 34 Vasculature Promote intravasation Anti-angiogenesis Suppress intravasation 35 , 36 Vascular normalization Reduce vascular permeability 37 Combine anti-angiogenesis with cytotoxic therapeutic approaches 38 , 39 Platelets Enhance angiogenesis and vascular permeability Targeted depletion of intratumoral platelets Enhance the accumulation of therapeutic agents 40 Protect CTCs Cut off the interactions between tumor cells and platelets Suppress tumor invasion 41 Reduce the survival rate of CTCs 41 Extracellular matrix Promote invasion and migration …”
Section: Targeting the Primary Soil By Nano-dds: Preventing The Metastatic Disseminationmentioning
confidence: 99%